2023
DOI: 10.1186/s12886-022-02674-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantify retinal structure in high-altitude residents with and without high altitude polycythemia

Abstract: Background To assess retinal structural parameters in high-altitude (HA) residents with and without high altitude polycythemia (HAPC) and to elucidate the relationship between retinal structural parameters and hemoglobin (HGB). Methods This cross-sectional study included 55 HAPC patients and 52 healthy HA residents. Retinal structural parameters included retinal nerve fiber layer (RNFL) thickness, optic nerve head (ONH) parameters and retinal vesse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The assessment of the optic nerve head (ONH) is crucial in evaluating and diagnosing numerous ocular conditions, including myopia, glaucoma and optic nerve oedema, which result in structural changes in the posterior globe. In addition, studies have shown that retinal vascular calibre changes are related to different ocular conditions, 23 24 and that anatomic relationships exist between the ONH and retinal vasculature. 25 Fundus examination of individuals with high hyperopia often shows crowding of the optic disc due to a small disc size in adult populations.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the optic nerve head (ONH) is crucial in evaluating and diagnosing numerous ocular conditions, including myopia, glaucoma and optic nerve oedema, which result in structural changes in the posterior globe. In addition, studies have shown that retinal vascular calibre changes are related to different ocular conditions, 23 24 and that anatomic relationships exist between the ONH and retinal vasculature. 25 Fundus examination of individuals with high hyperopia often shows crowding of the optic disc due to a small disc size in adult populations.…”
Section: Introductionmentioning
confidence: 99%